Tinjauan Literatur Sistematis: Faktor-Faktor Anteseden yang Memengaruhi Kesejahteraan Psikologis Guru di Indonesia - Rizki Faiz Kurniawan; Abdul Mujib (EduInovasi: Journal of Basic Educational Studies, 2025)
Teachers’ psychological well-being is a crucial aspect in maintaining the quality of teaching and the sustainability of the teaching profession, particularly in the context of increasing administrative demands, dynamic educational policy changes, and the accelerated adaptation to technology. This study aims to systematically synthesize empirical findings on the factors influencing teachers’ psychological well-being in Indonesia. A systematic literature review (SLR) was conducted following the PRISMA guidelines. Literature searches were carried out using Google Scholar, PubMed, Crossref, and Garuda databases with the assistance of Publish or Perish and Covidence software. Of the 477 articles initially identified, 18 met the inclusion criteria and were analyzed in depth. The findings indicate that teachers’ psychological well- being is shaped by a dynamic interaction between individual, organizational, and socio-spiritual factors. At the individual level, personal psychological resources such as self-efficacy, self-compassion, conscientiousness, emotional intelligence, emotion regulation, and resilience play a critical role in helping teachers manage professional demands adaptively. At the organizational level, quality of work life, job satisfaction, job security, work stress, and technostress emerge as significant structural determinants. Transformational leadership of school principals contributes to creating a supportive work climate and strengthening teachers’ psychological well-being, both directly and through improvements in the organizational climate. In addition, social support and religiosity function as sources of meaning and psychological buffers, particularly within the Indonesian cultural context.